Development of Parkinsonism in a Patient with Central Pontine Myelinolysis - Annibale Antonioni; Vittorio Rispoli; Patrik Fazio; Nico Golfrè Andreasi; Vittorio Govoni; Enrico Granieri (MDPI AG, 2022)
Osmotic demyelination syndrome (ODS) is caused by damage to the pons myelin sheath and nerve cells. Although the pathophysiological mechanism responsible for the damage is not yet fully understood, it is currently believed that osmotic-type changes (especially if they are massive and too rapid) cause oedema that leads to compression and, subsequently, demyelination of white matter fibres. It generally manifests with acute paraparesis/tetraparesis, dysphagia, dysarthria, diplopia, and loss of consciousness, as well as hallucinations, spasms, and other neurological symptoms related to brainstem damage. In extreme cases, the locked-in syndrome may also appear. Of note, in some cases an association between osmotic demyelinating damage and the onset of movement disorders has been documented and, although the pathophysiology is still unknown, a correlation has been postulated between ODS and movement disorders. Here, we present a patient with ODS who developed parkinsonism, thus supporting the hypothesis of a correlation between these pathological events.